(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
This study’s objective is to investigate the effect of incorporating corn cob powder (CCP) on the physicochemical and sensory acceptability of kuih kaswi. Kuih kaswi was prepared in formulations (control A 0% CCP (corn cob powder): 100% WF (wheat flour), B 5% CCP (corn cob powder): 95% WF, C 10% CCP: 90% WF, D 15% CCP: 85% WF, E 20% CCP: 80% WF and F 25% CCP: 75% WF). Results shows that the pH of kuih kaswi ranges from 7.08 to 7.35. The colour profile L* values range from 23.75 to 25.60, a* values range from 4.96 to 5.23 and b* values range from 6.15 to 6.53. The texture profile also shows significant changes, but the sensory evaluation result shows the acceptability of panels towards the addition of CCP in kuih kaswi. As a result, this research successfully managed to improve the physicochemical properties and fibre in kuih kaswi with the incorporation of CCP.